Soluble CD52 is an indicator of disease activity in chronic lymphocytic leukemia. Issue 10 (3rd October 2017) - Vojdeman, Fie J.; Herman, Sarah E. M.; Kirkby, Nikolai; Wiestner, Adrian; van t' Veer, Mars B.; Tjønnfjord, Geir E.; Itälä-Remes, Maija A.; Kimby, Eva; Farooqui, Mohammed Z.; Polliack, Aaron; Wu, Ka Lung; Doorduijn, Jeanette K.; et al.
Abstract: CD52 is a glycoprotein expressed on normal as well as leukemic immune cells and shed as soluble CD52 (sCD52). We studied sCD52 levels in three CLL cohorts: the 'early', the 'high-risk', and the 'ibrutinib-treated'. The 'high-risk' patients had significantly higher sCD52 levels than the 'early' patients. For the 'early' patients, high sCD52 levels were associated with a significantly shorter time to first treatment. Regarding prognostic factors, no clear correlations with stage, IGHV, or beta-2-microglobulin were found; in a cox multivariate analysis of the 'early' patients, sCD52 and IGHV both had independent prognostic value. Following chemo-immunotherapy, sCD52 decreased in parallel with leukocytes while during ibrutinib treatment and ibrutinib-induced ymphocytosis, sCD52 decreased along with lymph node reductions. In vitro IgM stimulation of CLL cells led to increased sCD52 levels in the medium. Our findings indicate that sCD52 reflects disease activity and potentially treatment efficacy in CLL.